Persisting mixed cryoglobulinemia in Chikungunya infection. - Manuela Oliver; Marc Grandadam; Catherine Marimoutou; Christophe Rogier; Elisabeth Botelho-Nevers; Hugues Tolou; Jean-Luc Moalic; Philippe Kraemer; Marc Morillon; Jean-Jacques Morand; Pierre Jeandel; Philippe Parola; et al. (Public Library of Science (PLoS), 2009)
BACKGROUND: Chikungunya virus (CHIKV), an arbovirus, is responsible for a two-stage disabling disease, consisting of an acute febrile polyarthritis for the first 10 days, frequently followed by chronic rheumatisms, sometimes lasting for years. Up to now, the pathophysiology of the chronic stage has been elusive. Considering the existence of occasional peripheral vascular disorders and some unexpected seronegativity during the chronic stage of the disease, we hypothesized the role of cryoglobulins. METHODS: From April 2005 to May 2007, all travelers with suspected CHIKV infection were prospectively recorded in our hospital department. Demographic, clinical and laboratory findings (anti-CHIKV IgM and IgG, cryoglobulin) were registered at the first consultation or hospitalization and during follow-up. RESULTS: Among the 66 travelers with clinical suspicion of CHIKV infection, 51 presented anti-CHIKV IgM. There were 45 positive with the serological assay tested at room temperature, and six more, which first tested negative when sera were kept at 4 degrees C until analysis, became positive after a 2-hour incubation of the sera at 37 degrees C. Forty-eight of the 51 CHIKV-seropositive patients were screened for cryoglobulinemia; 94% were positive at least once during their follow-up. Over 90% of the CHIKV-infected patients had concomitant arthralgias and cryoglobulinemia. Cryoglobulin prevalence and level drop with time as patients recover, spontaneously or after short-term corticotherapy. In some patients cryoglobulins remained positive after 1 year. CONCLUSION: Prevalence of mixed cryoglobulinemia was high in CHIKV-infected travelers with long-lasting symptoms. No significant association between cryoglobulinemia and clinical manifestations could be evidenced. The exact prognostic value of cryoglobulin levels has yet to be determined. Responsibility of cryoglobulinemia was suspected in unexpected false negativity of serological assays at room temperature, leading us to recommend performing serology on pre-warmed sera.